Arctic passages: liminality, Iñupiat Eskimo mothers and NW Alaska communities in transition - Schwarzburg, Lisa Llewellyn (Co-Action Publishing, 2013)
BACKGROUND: While the primary goal of the NW Alaska Native maternal transport is safe deliveries for mothers from remote villages, little has been done to question the impact of transport on the mothers and communities involved. This study explores how presence of Iñupiat values influences the desire of indigenous women of differing eras and NW Alaska villages to participate in biomedical birth, largely made available by a tribal health-sponsored transport system. OBJECTIVE: This paper portrays how important it is (and why) for Alaska Native families and women of different generations from various areas of Iñupiat villages of NW Alaska to get to the hospital to give birth. This research asks: How does a community's presence of Iñupiat values influence women of different eras and locations to participate in a more biomedical mode of birth? DESIGN: Theoretical frameworks of medical anthropology and maternal identity work are used to track the differences in regard to the maternal transport operation for Iñupiat mothers of the area. Presence of Iñupiat values in each of the communities is compared by birth era and location for each village. Content analysis is conducted to determine common themes in an inductive, recursive fashion. RESULTS: A connection is shown between a community's manifestation of Iñupiat cultural expression and mothers’ acceptance of maternal transport in this study. For this group of Iñupiat Eskimo mothers, there is interplay between community expression of Iñupiat values and desire and lengths gone to by women of different eras and locations. CONCLUSIONS: The more openly manifested the Iñupiat values of the community, the more likely alternative birthing practices sought, lessening the reliance on the existing transport policy. Conversely, the more openly western values are manifested in the village of origin, the less likely alternative measures are sought. For this study group, mothers from study villages with openly manifested western values are more likely to easily acquiesce to policy, and “make the best” of their prenatal travel.